2007
DOI: 10.1038/oby.2007.176
|View full text |Cite
|
Sign up to set email alerts
|

A Green Tea Extract High in Catechins Reduces Body Fat and Cardiovascular Risks in Humans

Abstract: NAGAO, TOMONORI, TADASHI HASE, AND ICHIRO TOKIMITSU. A green tea extract high in catechins reduces body fat and cardiovascular risks in humans. Obesity. 2007; 15:1473-1483. Objective: The body fat reducing effect and reduction of risks for cardiovascular disease by a green tea extract (GTE) high in catechins was investigated in humans with typical lifestyles. Research Methods and Procedures: Japanese women and men with visceral fat-type obesity were recruited for the trial. After a 2-week diet run-in period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
322
6
22

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(377 citation statements)
references
References 17 publications
27
322
6
22
Order By: Relevance
“…In all but one study, 17 subjects were randomly assigned to two conditions, with seven studies 10,15-20 using a true placebo group and the remaining four studies [11][12][13][14] comparing a high with a low dose of an EGCG-caffeine mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all but one study, 17 subjects were randomly assigned to two conditions, with seven studies 10,15-20 using a true placebo group and the remaining four studies [11][12][13][14] comparing a high with a low dose of an EGCG-caffeine mixture.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] On the other hand, studies with Caucasian subjects reported mixed results. [18][19][20] Moreover, the amount of regular caffeine intake may also influence the effectiveness of catechins.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors found reduction of cholesterol in mice (KIM et al, 2009;RICHARD et al, 2009), while others did not find any difference (FARDET et al, 2008;ZHENG et al, 2004). The controversy also exists in clinical studies showing beneficial (HSU et al, 2008;NAGAO;HASE;TOKIMITSU, 2007) or no effect on blood cholesterol (MAKI et al, 2009) after green tea supplementation. Since antioxidant agents such as green and white tea do affect quantitatively the circulating lipoproteins and cholesterol, it is not surprising that they did not affect blood concentration of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also observed increased excretion of lipids after ingestion of a mixture of these teas. Although some studies have not shown the effect of catechins on the reduction of triacylglycerols (KIM et al, 2009;NAGAO;HASE;TOKIMITSU, 2007), the available literature on green tea and its catechins shows that it can improve the lipid profile by decreasing the luminal hydrolysis of lipids and thereby reduce its intestinal absorption (BABU; LIU, 2008;KOO;NOH, 2007). Furthermore, it has been reported that catechins regulate the expression of hepatic LDL receptors modulating the lipid synthesis, excretion, and intracellular processing (BABU; LIU, 2008;KOO;NOH, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Green tea extracts in Japanese subjects with visceral obesity led to reductions in systolic blood pressure however the CV risk status of the included subjects is not clear (27). Conversely, increases in systolic blood pressure were seen with a combination of vitamin c and grape-seed polyphenols in a study of treated hypertensives (28).…”
Section: Discussionmentioning
confidence: 95%